HAMBATAN KOMUNIKASI PADA MAHASISWA PERANTAUAN LUAR JAWA DI KAMPUS UNIVERSITAS 17 AGUSTUS 1945 SURABAYA (STUDI DESKRIPTIF TENTANG KOMUNIKASI ANTAR BUDAYA DI KALANGAN MAHASISWA PERANTAUAN DARI LUAR JAWA DALAM MENGHADAPI CULTURE SHOCK DI UNIVERSITAS 17 AGUSTUS 1945 SURABAYA) - Putra, Yudha Priyan; Darmawan, Arif; Rochim, Achludhin Ibnu (Universitas 17 Agustus 1945 Surabaya, 2018)
This study aims to see how the communication barrier on the outside Java dispersed abroadstudents at the University of Surabaya August 17, 1945, in adapting when faced of culture shock.Culture Shock is a social phenomenon experienced by immigrants when relocate and inhabit areaswith different cultures. This study uses the concepts and theories of Intercultural Communication. Thisstudy uses a snowball and purposive sampling method in selecting informant, and then analyzed byusing interactive analysis. In this study, known any obstacles in communicating to different cultures,and the factors that become such inhibitors, as well as a supporting factor for student immigrants toremain in the overseas. Target is the students immigrants in UNTAG Surabaya, in order to adapt tothe other students and can unify the existing differences.Keywords: Barriers to communication, adaptation, intercultural communication